Breaking the conflict trap: civil war and development policy. - Collier, P; Elliott, V; Hegre, H; Hoeffler, A; Reynal-Querol, M; Sambanis, N (World Bank, 2003)
Civil war conflict is a core development issue. The existence of civil war can dramatically slow a country's development process, especially in low-income countries, which are more vulnerable to civil war conflict. When development succeeds, countries become safer; when development fails, countries experience greater risk of being caught in a conflict trap. Ultimately, civil war is a failure of development. This book identifies the dire consequences that civil war has on the development process and offers three main findings: (i) civil wars have adverse ripple effects, which are often not taken into account by those determine when to start or end a war; (ii) some countries are more likely than others to experience civil war conflict and therefore the risks of civil war differ considerable according to a country's characteristics including its economic stability. Finally, this book explores viable international measures that can be taken to reduce the global incidence of civil war and propose a practical agenda for action. This book will also be of great interest to researchers, academics, and anyone interested in conflict and post-conflict resolution.